Suggesting a Family Adoption Communication Model for Spouses Planning Child Adoption - Winda Hardyanti; Pawito Pawito; Prahastiwi Utari; Ahmad Zuber (Ianna Journal of Interdisciplinary Studies, 2024)
Background: Child adoption requires communication readiness guidance. For this reason, a suitable adoption communication model must be formulated for couples who will carry out the adoption process.